Proceedings of the 19th ACM Conference on Computer-Supported Cooperative Work &Amp; Social Computing 2016
DOI: 10.1145/2818048.2819984
|View full text |Cite
|
Sign up to set email alerts
|

Remixing as a Pathway to Computational Thinking

Abstract: Theorists and advocates of "remixing" have suggested that appropriation can act as a pathway for learning. We test this theory quantitatively using data from more than 2.4 million multimedia programming projects shared by more than 1 million users in the Scratch online community. First, we show that users who remix more often have larger repertoires of programming commands even after controlling for the numbers of projects and amount of code shared. Second, we show that exposure to computational thinking conce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 33 publications
2
67
2
4
Order By: Relevance
“…al. [69] found that users who use Scratch's remix tool, which allows users to take projects made by others and change them, have larger repositories of programming commands. This is even true after controlling for the number of projects and amount of code shared.…”
Section: Scratchmentioning
confidence: 99%
“…al. [69] found that users who use Scratch's remix tool, which allows users to take projects made by others and change them, have larger repositories of programming commands. This is even true after controlling for the number of projects and amount of code shared.…”
Section: Scratchmentioning
confidence: 99%
“…Driven by the advent of open platforms and communities on the internet, it has only been in recent years that the concept of innovation through recombination has gained further attention (Lessig, 2008;Khatib et al, 2011;Tuite and Smith, 2012;Cheliotis et al, 2014;Sapsed and Tschang, 2014;Oehlberg et al, 2015;Dasgupta et al, 2016;Stanko, 2016). Online platforms with openly licensed content and data make it increasingly easy to share and access a wide range of usergenerated ideas (Lee et al, 2010;Kane and Ransbotham, 2012;Leonardi, 2014;Payton, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Dasgupta et al [7] have shown that remixing can be beneficial in learning computational thinking concepts. Their analysis is based on two hypotheses that largely measure the growth in the number of programming block types ("repertoire"), and the use of particular programming concepts.…”
Section: Repertoire Analysismentioning
confidence: 99%
“…Remixing in Scratch has been the recipient of much attention and the idea of peer supported learning clearly has merit, but results have been mixed so far. Remixing has been shown to promote learning [7] but there is also a danger that if there is poor coding style or hidden bugs in a project, these might also propagate to remixed projects and contribute in learning bad programming practices, contrary to the goal of remixing [8]. In this study we build upon the results from prior studies on remixing in Scratch, and attempt to present a clearer picture through measuring the use of elementary patterns in remixes.…”
Section: Introductionmentioning
confidence: 99%